Comparative Study of Basic Education in Indonesia and Finland - Rahma Rahma; Habibburrahman Habibburrahman; Ahmad Mauluddin; Rizki Ananda (JURNAL PENDIDIKAN IPS, 2024)
This research aims to compare the basic education systems between Indonesia and Finland. The research method used is literature study with a qualitative approach. Data was obtained through literature analysis, including books, scientific journals, articles and research reports that are relevant to the topic being researched. The research results show that the education system in Finland has advantages in terms of strong government support, free education for all teachers, high teacher qualifications, and collaboration between society, teachers and students. On the other hand, Indonesia faces challenges in implementing education, including transparent monitoring and evaluation, harmony between the school environment, family and community, and teacher qualifications that are not yet optimal. This study provides an understanding of best practices that can be adopted by both countries to improve education and the preparation of competent human resources in the future.